The emergence of Jewish Ghettos during the Holocaust - Mikhman, Dan 1947- (Cambridge University Press [u.a.], 2011)
"This book is a linguistic-cultural study of the emergence of the Jewish ghettos during the Holocaust. It traces the origins and uses of the term 'ghetto' in European discourse from the sixteenth century to the Nazi regime. It examines with a magnifying glass both the actual establishment of and the discourse of the Nazis and their allies on ghettos from 1939 to 1944. With conclusions that oppose all existing explanations and cursory examinations of the ghetto, the book impacts overall understanding of the anti-Jewish policies of Nazi Germany"--